Comprehensive detection method and assessment of karst development characteristics of diversion aqueduct: A Case Study in Yunnan, China - Li, Zhi-Qiang; Yan, Haoxuan; Nie, Lichao; Chen, Andong; Zhang, Duo; Sun, Xingbang (Journal of applied geophysics, 2025)
Due to the complex karst geological structure, the construction of diversion aqueducts in karst formations poses deformation and stability challenges for the foundation. During the construction of the aqueduct in Jifu Village, Yunnan Province, a comprehensive detection method was employed to investigate the karst development in the area. This method integrates information obtained from various techniques, including geological analysis, Ground Penetrating Radar (GPR), and drilling. Geological analysis was used to identify potential karst development locations within the project area. GPR provided geophysical profiles revealing shallow karst features, and drilling was strategically placed along these profiles to verify and supplement the GPR data. This approach yielded more accurate information on karst development. The results demonstrate that the combination of geological analysis, geophysics, and drilling can effectively detect karst formations. The identified karst locations were consistent with the inferred underground karst zones from the investigation. Optimizing and refining this method can offer valuable reference and guidance for detecting karst areas in similar regions. •The karst development area was delineated using a comprehensive detection method.•This method integrates geological analysis, Ground Penetrating Radar (GPR), and drilling.•3D representations of GPR data and 2D profiles from drilling were created for the study area.•A detailed evaluation of the karst development characteristics was conducted.